Chapter 5 Communicating the Country-of- Origin in Advertising Semiotic Persuasion - Szczęsna, Ewa (Taylor & Francis, 2024)
This chapter argues for the significance of semiotic organisation of messaging in communicating the country-of-origin (COO) of a brand in advertising, and ultimately-brand itself. The author analyses persuasive structures of human thought used in visual advertising. Metaphorical thinking, narrativisation, using stereotypes, mythisation, and the accompanying aestheticisation in advertising become strategies shaping the way consumers perceive products/brands and in consequence- shape purchase intentions. The adoption of these strategies in the semiotic layer of messaging (selection of colours, shapes, chiaroscuro, elements` composition) strengthens their efficiency. Semiotic persuasion allows for the polysensory engagement of the recipient, camouflaging overt persuasion, connect the COO with the target country. With reference to examples of visual advertisements, this chapter discusses the use of properties of the analysed strategies in shaping the persuasive efficiency of advertisements based on the COO effect. It analyses how the social beliefs on the COO represented in the semiotic layer of messaging define a brand and how the representations of a brand influence beliefs on the COO- and how they can change them. Finally, this chapter presents marketing as an important component of culture anchored not only in economy, but also in semiotics, rhetoric of image, psychology of perception, and social communication.